PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA GAMBAR PADA MATERI SISTEM PERNAPASAN TERHADAP HASIL BELAJAR SISWA SMP NEGERI 1 HILISALAWA’AHE - Gulo, Yeni Chrisanti (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
The point of this examination is to decide the impact of the disclosure learning model on the respiratory framework material. This kind of exploration utilizes semi trial research (semi analyze). Semi exploratory examination is research planned to decide if there are ramifications of something forced regarding the matters being contemplated. The quantity of members in this survey is class VIII-An and class VIII-B of SMP Negeri 1 Hilisalawa'ahe. This exploratory data is examined utilizing sensibility tests and hypothesis tests. This shows that there is an impact of the revelation learning model on learning results. Since this learning model is compelling in additional creating understudy learning results. The thought set forward by specialists is: open learning ought to be utilized as the learning model of decision in growing further learning results since it can make understudies dynamic in conveying contemplations or ends and can additionally foster understudy learning results in learning. Future experts should finish this test with a more extensive degree